1980
DOI: 10.1177/00220345800590120801
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability of New Composite Restorative Materials Under Accelerated Aging

Abstract: The color stability of seven commercial composite restorative materials under conditions of accelerated aging was evaluated by reflection spectrophotometry at baseline and 300, 600, and 900 h. During early aging the composites generally became darker, more chromatic, and more opaque. Changes in color of the conventional composites during aging were influenced by erosion of the resin matrices and exposure of filler particles. Color stability of the microfilled composites under the in vitro conditions tested was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0
5

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 1 publication
9
41
0
5
Order By: Relevance
“…Such change has been previously reported in the literature 3,4,5,6,15,16 . The problem in the evaluation of the results from this type of test is the limit in the ability to detect differences.…”
Section: Discussionsupporting
confidence: 83%
“…Such change has been previously reported in the literature 3,4,5,6,15,16 . The problem in the evaluation of the results from this type of test is the limit in the ability to detect differences.…”
Section: Discussionsupporting
confidence: 83%
“…11,12 It was reported that if the kinetic of dimethacrylate monomer is limited, polymerization cannot increase any more, but if temperature rises, the kinetic of dimethacrylate monomer increases and the flexibility of polymer chain in the network is enhanced, and as a result, the degree of polymerization increases by post cure. 13 Power et al 14,15 reported that after accelerated aging under xenon light and 90 percent relative humidity, the matrices of resin eroded away and the filler was exposed, and as a result, the resin showed chalky surface and the roughness of the surface increased. 16 The absorption of water by composite resin is affected by the hydrophobic of the resin matrix.…”
Section: Discussionmentioning
confidence: 99%
“…And our results of the visual examination and SEM observation of changes caused by accelerated aging were consistent with the reports of Power et al above. 14,15 Occurrence of numerous microcracks and defects on the surface of SYNERGY Duo and TESCERA ATL after accelerated aging is probably because of the erosion of the resin matrix, hydrolysis of the fillers and polymerization shrinkage related to additional polymerization involving xenon light, heat, etc. Microcracks were much wider and longer in SYNERGY Duo than in TESCERA ATL, and the surface of SYNERGY Duo had many changes including the exposure of fillers over the substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrinsic factors for discoloration include staining by adsorption or absorption of colorants as a result of contamination from exogenous sources such as coffee, tea, and beverages [21][22][23] . Extrinsic factors include mechanical wear, microleakage, incomplete adhesion of composite resins and teeth, and rough surface [24][25][26][27] . Barkmeier and Cooley 28) were reported that the rougher of composite resin surface, the higher chance of staining and discoloration.…”
Section: ⅰ Introductionmentioning
confidence: 99%